The Decreasing of the assistant time Required For Taking Off And Insertion Of The Work Pieces (Damascus University Journal for engineering sciences, 2021)
Trying to shorten the assistant time by using a special set for f feeding and removal of worked on items, on public lathes to produce a pillar, through two working cutting strokes, and defined dimensions, the pillar will be used to hold electric motors for fans. Feeder's time has been calculated, in addition to calculating the time of removal and tightening, comparing them to the time, this is reflected positively on the increase of productivity, effectively and remarkably. This also raises the better investment of public machines, the thing that decreases the cost of the product, and supports competition on local level at least. This study may be copied on similar parts using suitable feeders; also, it could be used not only for public machines but also on semi-machine lathes. Also all parts of feeders were accounted, beginning from funnel volume to suit the operating machine, ending with knowing the motor power required for the feeders. The work-piece is ejected through a spring to be fixed in the cavity side of the central axis of the machine near the machine case, so when the case is dismantled the work-piece will be automatically ejected, without consuming but a tiny part of a second. This pace is considered important for automation of local manufacturing production machines.
Keywords: assistant time; public lathes; the pillar; the electric fans; automation